Enhancing Certified Vocational Teachers' Citizenship Behavior: The Interplay of Ethical Leadership, Workplace Spirituality, and Local Culture in Indonesian Private SMK Schools (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study develops evidence-based strategies to enhance Organizational Citizenship Behavior (OCB) among certified teachers in Indonesian private vocational schools (SMK), examining the interplay between ethical leadership, workplace spirituality, and local cultural values (Soméah). Method: Using the POP-SDM methodology, this sequential exploratory mixed-methods research involved certified teachers from private SMK in Bogor Regency. Data collection included semi-structured interviews followed by surveys. Analysis employed SEM-PLS complemented by SITOREM for intervention development. Results: Significant relationships emerged between ethical leadership and OCB (β = 0.46, p < 0.001), with workplace spirituality as a key mediator. Soméah cultural values strongly influenced OCB (β = 0.51, p < 0.001). Psychological well-being, organizational trust, and work engagement showed interconnected effects, with the model explaining 72% of OCB variance. SITOREM prioritized ethical leadership development and cultural integration. Novelty: This research integrates Sundanese local wisdom (Soméah) into OCB frameworks for vocational education, simultaneously examining six variables through POP-SDM, offering culturally-grounded strategies for teacher behavior enhancement in Indonesian educational contexts.